Penguatan Kesadaran Sosial Masyarakat Melalui Pendampingan Kegiatan Rutinan Yasinan dan Tahlilan di Desa Tegalrejo, Pulung, Ponorogo - Salsa Bella Agustin; Mariana Mariana (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Assistance program for yasinan and tahlilan activities which are carried out regularly every week. Increasing social awareness of the community and establishing friendship so that it remains well established. The method used for this mentoring activity is a qualitative method. Where research is carried out by going directly to the object of research in order to get results that are in accordance with what is expected by the researcher. This activity was carried out in Tegalrejo Village, Pulung, Ponorogo, East Java. In this research, the main object is mothers who participate in yasinan and tahlilan activities. This research aims to increase public awareness through the activities of woman in the Yasinan and tahlilan congregations